RESULTS OF THE PHARMACOECONOMIC ANALYSIS OF THE USE OF A PNEUMOCOCCAL CONJUGATED 7-VALENT VACCINE FOR PREVENTION OF PNEUMOCOCCAL INFECTIONS IN CHILDREN DURING FIRST 5 YEARS OF LIFE IN THE RUSSIAN FEDERATION - A.A. Baranov; V.V. Omel'yanovskii; N.I. Briko; Yu.V. Lobzin; L.S. Namazova-Baranova; V.K. Tatochenko; S.M. Kharit; S.V. Sidorenko; I.S. Koroleva; A.E. Platonov; G.Yu. Moisyak; I.S. Krysanov; et al. (Union of pediatricians of Russia, 2009)
The article discusses the first results of a pharmacoeconomic analysis of the efficacy of using the Pneumococcal conjugated 7-valent vaccine (PCV7) for immunization of children aged 2 months to 5 years in Russia using techniques for modeling various approaches to cohort immunization. It shows clinical and economic efficacy of implementing routine immunization in children during first 5 years against pneumococcal infection using PCV7 given direct and indirect costs. It justifies the expediency of incorporating vaccination against pneumococcal infection in children aged 2 months up into the Russian National Immunization Schedule.Key words: pharmacoeconomic analysis, children during first 5 years of life, vaccination, pneumococcal conjugated 7-valent vaccine